Hornbill abundance and breeding incidence in relation to habitat modification and fig fruit availability. (14th November 2020) - Pawar, Pooja Yashwant; Mudappa, Divya; Raman, T. R. Shankar
Abstract : Asian hornbills are known to forage and breed in fragmented rainforests and agroforestry plantations in human‐modified landscapes adjoining contiguous protected forests. However, the factors influencing year‐round hornbill abundance, demography and tracking of key food resources such as wild fig Ficus fruits in modified habitats and protected forests remain poorly understood. We carried out monthly surveys of two species of high conservation concern, the Vulnerable Great Hornbill (GH, Buceros bicornis ) and the endemic Malabar Grey Hornbill (MGH, Ocyceros griseus ) for 15 months and monitored ripe fig fruit availability for 12 months along 11 line transects (total length 24 km) in shade‐coffee plantations and adjoining continuous rainforests in a protected area (PA) in the Anamalai Hills, Western Ghats, India. Both hornbill species used plantations and the PA year‐round but distance sampling density estimates were higher in the PA in both nesting (GH by 57%; MGH by 50%) and non‐nesting (GH by 53%; MGH by 144%) seasons. Relative to estimates from 2004 to 2005, mean GH density appeared stable or increasing, whereas MGH had declined by 39% in the PA and by 56% in plantations. Monthly encounter rate of both hornbills tended to be higher in the PA and that of MGH was also positively related to the density of fig trees with ripe fruit. Sex ratios of observed adult birds in the non‐nesting season were relatively even (GH) or slightly female‐biased (MGH), but became male‐biased in both species during the nesting season when females were confined in tree‐cavity nests. We used change in the adult sex ratio of observed birds from the non‐nesting to nesting season to estimate an index of the proportion of adult pairs breeding at any point within the season, providing the first such estimates for any hornbill species. The proportion of breeding pairs was higher in the PA (GH – 56%, MGH – 64%) than in the plantations (GH – 33%, MGH – 30%). Although hornbills use shade‐coffee plantations year‐round, partly due to fig fruit availability, differences in hornbill density and breeding incidence, as assessed from the sex ratios of observed adult birds, indicate that plantations are a sub‐optimal habitat for both species.